Effect of DAPAgliflozin on Myocardial Fibrosis and Ventricular Function in Patients with ST-Segment Elevation Myocardial Infarction—DAPA-STEMI Trial - Ortega-Paz, Luis; Laudani, Claudio; Sionis, Alessandro; Vidal-Cales, Pablo; Arevalos, Victor; Andrea, Rut; Morr, Carlos Igor; De Diego, Oriol; Ortega, Emilio; Jimenez-Trinidad, Francisco-Rafael; Dantas, Ana Paula; Angiolillo, Dominick J.; et al. (Journal of cardiovascular development and disease, 2025)
Background: Myocardial fibrosis leads to ventricular dysfunction and worsened prognosis, especially after ST-segment elevation myocardial infarction (STEMI). Sodium–glucose cotransporter 2 inhibitors (SGLT2is) offer cardiovascular benefits by reducing markers of myocardial fibrosis and fibroblast activity. However, the effects of SGLT2i on myocardial fibrosis deposition among STEMI patients undergoing primary percutaneous coronary intervention (PCI) have not yet been evaluated. Study and Design: The effect of DAPAgliflozin on myocardial fibrosis and ventricular function in patients with STEMI (DAPA-STEMI) trial is a phase III, multicenter, randomized, double-blind, placebo-controlled trial. The study aims to assess the effects of dapagliflozin on myocardial fibrosis and ventricular function, evaluated using cardiac magnetic resonance (CMR), in STEMI patients undergoing primary PCI. Eligible patients were 30 to 85 years old and exhibited a left ventricular ejection fraction ≤ 50%. A total of 120 patients with STEMI were expected to be randomized 1:1 to receive dapagliflozin 10 mg or placebo daily for six months. The primary endpoint is the change in the extracellular volume fraction of the remote myocardium from baseline to six months, as measured by CMR. The secondary endpoints include changes in the circulating C-terminal propeptide of type I procollagen, N-terminal propeptide of type III procollagen, and Galectin-3 from baseline to six months. The study was stopped prematurely due to slow recruitment, with 54 enrolled patients, limiting the statistical power to detect changes in the primary endpoint between groups. Conclusions: The DAPA-STEMI trial will provide insights into the impact of dapagliflozin on myocardial fibrosis and ventricular remodeling in patients with STEMI undergoing primary PCI. Clinical Trial Registration Unique Identifier: NCT06619600